HPLC Method for Analysis of Lercanidipine Hydrochloride in Tablets - G. MUBEEN; MAMTA PAL; M.N. VIMALA (International Journal of Pharma and Bio Sciences, 2010)
A reverse phase HPLC method was developed for quantitative determination of Lercanidipine hydrochloride in tablets. The separation was achieved by using 250 Χ 4.6mm Wakosil C18 (5µm) column with a mixture of methanol: acetonitrile (70:30) as a mobile phase, at a flow rate of 1.0ml/min. The detection was carried out at 219nm, and the retention time was found to be 4.10min. Linearity was observed in the concentration range of 10-60µg/ml. The mean recoveries obtained for lercanidipine HCl ranged from 96.38 to 101.23 %. The LOD and LOQ was found to be 0.03µg/ml and 0.04µg/ml respectively. The developed method was found to be accurate, precise and rapid for analysis of Lercanidipine HCl in tablets.